Proposal for a prospective multi-centre audit of chronic subdural haematoma management in the United Kingdom and Ireland. (April 2014) - Coulter, Ian C.; Kolias, Angelos G.; Marcus, Hani J.; Ahmed, Aminul I.; Alli, Saira; Al-Mahfoudh, Rafid; Borg, Anouk; Cowie, Christopher J. A.; Hill, Ciaran S.; Joannides, Alexis J.; Jones, Timothy L.; Kailaya-Vasan, Ahilan; et al.
Abstract Background. Chronic subdural haematoma (CSDH) is a common condition that increases in incidence with rising age. Evacuation of a CSDH is one of the commonest neurosurgical procedures; however the optimal peri-operative management, surgical technique, post-operative care and the role of adjuvant therapies remain controversial. Aim. We propose a prospective multi-centre audit in order to establish current practices, outcomes and national benchmarks for future studies. Methods. Neurosurgical units (NSU) in the United Kingdom and Ireland will be invited to enrol patients to this audit. All adult patients aged 16 years and over with a primary or recurrent CSDH will be eligible for inclusion. Outcome measures and analysis. The proposed outcome measures are (1) clinical recurrence requiring re-operation within 60 days; (2) modified Rankin scale (mRS) score at discharge from NSU; (3) morbidity and mortality in the NSU; (4) destination at discharge from NSU and (5) length of stay in the NSU. Audit standards have been derived from published systematic reviews and a recent randomised trial. The proposed standards are clinical recurrence rate < 20%; unfavourable mRS (4–6) at discharge from NSU < 30%; mortality rate in NSU < 5%; morbidity rate in NSU < 10%. Data will be submitted directly into a secure online database and analysed by the study's management group. Conclusions. The audit will determine the contemporary management and outcomes of patients with CSDH in the United Kingdom and Ireland. It will inform national guidelines, clinical practice and future studies in order to improve the outcome of patients with CSDH.